2019
DOI: 10.1111/mec.15252
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Wolbachia cidB gene, but not cidA, is associated with cytoplasmic incompatibility mod phenotype diversity in Culex pipiens

Abstract: Endosymbiotic Wolbachia bacteria are, to date, considered the most widespread symbionts in arthropods and are the cornerstone of major biological control strategies. Such a high prevalence is based on the ability of Wolbachia to manipulate their hosts' reproduction. One manipulation called cytoplasmic incompatibility (CI) is based on the death of the embryos generated by crosses between infected males and uninfected females or between individuals infected with incompatible Wolbachia strains. CI can be seen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 47 publications
4
72
1
Order By: Relevance
“…Several recent breakthrough studies have collectively identified Wolbachia-encoded genes (of viral origin) that contribute to the induction and rescue of CI (Beckmann et al, 2017;LePage et al, 2017;Bonneau et al, 2018Bonneau et al, , 2019Lindsey et al, 2018;Shropshire et al, 2018;Beckmann et al, 2019c;Chen et al, 2019;. Wolbachia-encoded genes that rescue CI are labeled as cifA, cidA, or cindA, depending on whether they rescue a defect caused by deubiquitylase (d), nuclease (n), both (nd); "f " is used by certain authors and/or when the nature of the defect is unknown (see Beckmann et al, 2019a,b;.…”
Section: The Influence Of Wolbachia On Host Ecologymentioning
confidence: 99%
“…Several recent breakthrough studies have collectively identified Wolbachia-encoded genes (of viral origin) that contribute to the induction and rescue of CI (Beckmann et al, 2017;LePage et al, 2017;Bonneau et al, 2018Bonneau et al, , 2019Lindsey et al, 2018;Shropshire et al, 2018;Beckmann et al, 2019c;Chen et al, 2019;. Wolbachia-encoded genes that rescue CI are labeled as cifA, cidA, or cindA, depending on whether they rescue a defect caused by deubiquitylase (d), nuclease (n), both (nd); "f " is used by certain authors and/or when the nature of the defect is unknown (see Beckmann et al, 2019a,b;.…”
Section: The Influence Of Wolbachia On Host Ecologymentioning
confidence: 99%
“…Sequence divergence in CI-associated factors has long been thought to be a contributing factor to these incompatibilities, namely that divergence in both CI-causing and rescue-causing genes would be required for bidirectional CI to emerge (Charlat et al, 2001). Indeed, phylogenetic analyses of cif genes reveal that strains carrying similar alleles tend to be compatible, strains with more distantly related cif genes are not, and a single Wolbachia strain can have multiple unique cif gene pairs (Bonneau et al, 2018a(Bonneau et al, , 2019LePage et al, 2017). For instance, when wMel is transinfected into a D. simulans background, it is unidirectionally incompatible with the native wRi strain, wherein wRi can rescue wMel-induced CI but the reciprocal cross is incompatible (Poinsot et al, 1998).…”
Section: The Genetic Basis Of Bidirectional CI Remains Unknownmentioning
confidence: 99%
“…Thus, it is plausible that wRi can rescue wMel's CI because of CifAwRi[T1] whereas wMel cannot rescue wRi's CI because it lacks a rescue gene for the Type 2 gene pair (LePage et al, 2017). Additionally, population genetic analyses of cif genes in wPip reveal that there are numerous unique strains, each strain carries multiple closely related cif variants that belong to Type 1 and Type 4 cif clades, and a single genetic variant of CifBwPip[T1] correlates with the inability of one strain of wPip to rescue CI caused by a divergent wPip strain (Atyame et al, 2011b;Bonneau et al, 2018aBonneau et al, , 2019. However, while these data suggest that cif genetic variation and/or copy number contributes to strain incompatibility, it remains possible that the considerable host genotypic variation between these incompatible populations contributes to these relationships in a way that also correlates with cif genotypic diversity (Atyame et al, 2011a).…”
Section: The Genetic Basis Of Bidirectional CI Remains Unknownmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is plausible that wRi can rescue wMel's CI because of CifAwRi[T1] whereas wMel cannot rescue wRi's CI because it lacks a rescue gene for the Type 2 gene pair (LePage et al, 2017). Additionally, population genetic analyses of cif genes in wPip reveal that there are numerous unique strains, each strain carries multiple closely related cif variants that belong to Type 1 and Type 4 cif clades, and a single genetic variant of CifBwPip[T1] correlates with the inability of one strain of wPip to rescue CI caused by a divergent wPip strain (Atyame et al, 2011b;Bonneau et al, 2018aBonneau et al, , 2019. However, while these data suggest that cif genetic variation and/or copy number contributes to strain incompatibility, it remains possible that the considerable host genotypic variation between these incompatible populations contributes to these relationships in a way that also correlates with cif genotypic diversity (Atyame et al, 2011a).…”
Section: The Genetic Basis Of Bidirectional CI Remains Unknownmentioning
confidence: 99%